If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -4m = 10 Solving 15 + -4m = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -4m = 10 + -15 Combine like terms: 15 + -15 = 0 0 + -4m = 10 + -15 -4m = 10 + -15 Combine like terms: 10 + -15 = -5 -4m = -5 Divide each side by '-4'. m = 1.25 Simplifying m = 1.25
| 3X=6(1-x) | | 9-8y=41 | | -3n+6-7n=19 | | x^2-12=20 | | 12+9(3z-2)-15z= | | 2(2X+3)(X-5)=0 | | -2x+5-x=17 | | (x+1)(x+1)=2(x+1) | | -16=d+12 | | 16+x=43 | | 1(2X+3)(X-5)=0 | | 0(2X+3)(X-5)=0 | | x^2-1.6x=0 | | 4(m+3)=2m+12 | | (2b-4)(3b+6)=0 | | 1.5+x=1725 | | -1(2X+3)(X-5)=0 | | 2x=8x-9 | | -3+4x=37 | | 0.5(5-2h)=h/2 | | 5t+1=-2t-6 | | 6=4-2k | | -5x+6=-34 | | 4x-2=6x+6 | | 88=4+7x | | 23x+90=24 | | 5x^2+3=x^2+51 | | 6+4y=11 | | N+12=2n+8 | | 5x+(3x+3)= | | 7y+6+64+4y=180 | | 12x^2+80x-28=0 |